2009
DOI: 10.1055/s-0029-1214726
|View full text |Cite
|
Sign up to set email alerts
|

Argon plasma coagulation has a long-lasting therapeutic effect in patients with chronic radiation proctitis

Abstract: APC is highly effective in all patients with mild radiation proctitis and in the majority of those with severe disease, providing long-lasting clinical remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 11 publications
4
60
1
4
Order By: Relevance
“…Indeed, evidence comes from several retrospective and prospective case-series and observational studies, while only a few, small-sized RCTs comparing APC to formalin application have been conducted [49][50][51][52][53][54][55][56][57][58] . A systematic review focusing on studies published upon 2011 found that APC improved or completely resolved symptoms in 50% to 100% of patients [59] .…”
Section: Evidencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, evidence comes from several retrospective and prospective case-series and observational studies, while only a few, small-sized RCTs comparing APC to formalin application have been conducted [49][50][51][52][53][54][55][56][57][58] . A systematic review focusing on studies published upon 2011 found that APC improved or completely resolved symptoms in 50% to 100% of patients [59] .…”
Section: Evidencesmentioning
confidence: 99%
“…Severe complications have been rarely described, including gas explosion and perforation, fistula, stricture, and long-term pain [51,58,62] . Notably, colonic explosion mostly occurred when the endoscopic procedure was performed after inaccurate, local bowel cleansing with enemas, instead of gold-standard oral preparation [53,57] .…”
Section: Evidencesmentioning
confidence: 99%
“…It can occur from 9 months to 30 years after index treatment, although most patients present within 1 to 2 years of treatment. [71][72][73][74] Rectal bleeding is the leading sign of radiation proctopathy. The bleeding is rarely life threatening.…”
Section: Anal Fissurementioning
confidence: 99%
“…84 APC results in a decrease in rectal bleeding in 80% to 90% of patients and also may improve symptoms such as urgency and diarrhea. 85,86 In most cases, 1 to 3 treatment sessions are required. Power settings of 25 W to 60 W and flow rates of 0.5 L/minute to 2.5 L/minute have been reported.…”
Section: Anal Fissurementioning
confidence: 99%
“…Villavicencio et al demonstrated the successful short-term resolution of rectal bleeding after APC treatment in >90% of patients who previously did not respond to medical or other endoscopic therapies [98]. In other studies, success rates are between 83% and 100% after one to four APC sessions [99][100][101][102][103]. Complications of APC are low, and reported cases of rectal ulceration leading to fi stula development range from <1% to 2%.…”
Section: Treatment and Preventionmentioning
confidence: 99%